Patients' and GPs' duties and responsibilities in long-term care after myocardial infarction: a qualitative study of patients' perspectives. (30th June 2022) - Pohl, Jonathan; Heintze, Christoph; Herrmann, Wolfram J
Abstract: Background: Cardiovascular disease is one of the main causes of death in Europe and around the world. Effective and individualized long-term treatment of patients with chronic diseases such as cardiovascular disease and myocardial infarction reduces mortality and the risk of recurrence and prevents secondary disease. However, there is little data on patients' views. Objective: To examine patients' perspectives on long-term care after myocardial infarction. Methods: A qualitative interview study with patients after myocardial infarction in Berlin and Brandenburg, Germany. Fifteen episodic interviews were conducted, transcribed, coded, and analyzed using framework analysis. Results: Participants consistently emphasized major functions fulfilled by general practitioners: monitoring, advice, diagnosis, referral, coordination. Furthermore, other functions such as empathy and feeling emotionally valued. Major patient roles emerged such as information sharing, lifestyle change, and coping. Responsibility toward doctors was expressed in terms of active participation in describing their symptoms, following the doctor's directions, and sharing in decision-making. Self-responsibility in participants showed 2 contrasting approaches. On the one hand, a passive attitude (acceptance, helplessness), and on the other, active resistance and taking action. Conclusion: The study underlines the importance of communication and awareness of the patient's perspective. General practitioners must address patients' aims and fears, encourage their initiative, and focus on empathy and education.